The Importance of Sleep in Athletic Performance - A Systematic Review - Julia Białeta; Katarzyna Rowińska; Karolina Siembab; Michalina Jurkiewicz; Agnieszka Napieralska; Wiktor Garbarczyk; Albert Kapla; Alicja Černohorská; Wiktoria Pysiewicz; Daria Bednarczyk (Quality in Sport)
Introduction